Les observatoires de la mer et du littoral : du suivi des interactions hommes-milieux à la coordination des acteurs - Jean-Michel Salles; Hélène Rey Valette; Rémi Mongruel (Développement Durable et Territoires)
The development of integrated management policies in the coastal and maritime environment involves renewing the information systems in support of these policies. New indicators have been proposed for which it is necessary to study not only the methods of construction but also their legitimacy and the nature of the needs they meet. This article examines the issue of observatories in the maritime and coastal environment by studying the specificities of collecting information related to the complexity of the processes and the diversity of maritime issues. In addition, it also addresses the issue of data quality and the legitimacy of the standards against which monitoring is carried out. Finally, the relevance of the indicators in relation to the needs of managers is discussed, as well as the diversity of the observatories' functions, emphasizing their role in the coordination and support for governance.